2014
DOI: 10.1111/clr.12535
|View full text |Cite
|
Sign up to set email alerts
|

Deproteinized bovine bone remodeling pattern in alveolar socket: a clinical immunohistological evaluation

Abstract: Deproteinized bovine bone guarantees the activity of bone remodeling processes in human extraction socket at 5 months of healing, bringing to a higher expression of anabolic and catabolic bone markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…Similarly, [26] reported 57.75% of non-vital bone when using autogenous bone blocks. In the present investigation CCXBB was present in 21.4% of the samples after 26 weeks of healing, what is in agreement with previous studies reporting histological outcomes of other xenogeneic bone replacement grafts placed for the regeneration of extraction sockets [27, 28]. In this indication, the percentage of residual graft was 39.8 and 33.4%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, [26] reported 57.75% of non-vital bone when using autogenous bone blocks. In the present investigation CCXBB was present in 21.4% of the samples after 26 weeks of healing, what is in agreement with previous studies reporting histological outcomes of other xenogeneic bone replacement grafts placed for the regeneration of extraction sockets [27, 28]. In this indication, the percentage of residual graft was 39.8 and 33.4%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…ALP-positive cells were detectable, in all specimens on the periphery of MVB, associated to areas of new bone formation. These observations were also reported on a clinical study on guided bone regeneration (GBR) [41], as well as through the evaluation of the healing of particulate xenogeneic bone grafts (DBBM) [28]. Experimental research using immune-histochemical analysis for comparing early bone remodelling between autografts and allografts has reported comparable behavior for osteoprotegerin (OPG), alkaline phosphatase (ALP), collagen 1 (COLI), osteopontin (OPN), and osteocalcin (OSC), although an increased activity of tartrate-resistant acid phosphatase (TRAP) was seen in allogenic bone grafts [42].…”
Section: Discussionmentioning
confidence: 75%
“…Milani and colleagues have recently reported immunohistochemical expression of BMP2 and BMP7, not only intracellular, but also around xenograft particles in a socket preservation model in humans. 23 This phenomenon has been related in the literature regarding other proteins expression, as osteopontin or TRAP-1. 24 In the present study, regarding the expression of BMP-4 in function of the different grafting biomaterials studied (i.e., xenograft and allograft), it was observed that the remaining particles of anorganic bovine xenograft got impregnated with this protein, which might be related to the superior rate of bone formation promoted by this biomaterial as compared with the allograft alone.…”
Section: Discussionmentioning
confidence: 71%
“…Milani and colleagues have recently reported immunohistochemical expression of BMP2 and BMP7, not only intracellular, but also around xenograft particles in a socket preservation model in humans . This phenomenon has been related in the literature regarding other proteins expression, as osteopontin or TRAP‐1 .…”
Section: Discussionmentioning
confidence: 71%
“…Newly formed tissues were consistently in close proximity to DBBM, which is one of the most investigated scaffolds and is widely employed in regenerative procedures, both in animal models and in clinical practice [2829]. Many case series reported good clinical outcomes from DBBM blocks used in onlay [3031] and inlay procedures [3233].…”
Section: Discussionmentioning
confidence: 99%